Seasonal changes of commercial traits, proximate and fatty acid compositions of the scallop Flexopecten glaber from the Mediterranean Sea (Southern Italy) - Prato, Ermelinda; Biandolino, Francesca; Parlapiano, Isabella; Papa, Loredana; Denti, Giuseppe; Fanelli, Giovanni (PeerJ, 2019)
This study provides information on biological (gonadosomatic index), commercial quality (condition index and meat yield) and biochemical aspects (proximate composition, fatty acids) of the soft tissues of Flexopecten glaber reared in suspended cages in the Ionian Sea. The results showed that condition index (CI) and meat yield (MY) peaked in December (60 and 30%, respectively) and in April, May and June (from 53 to 60% for CI and from 34 to 36% for MY). Gonadosomatic index showed three main peaks in winter, spring and summer months. Contents of protein 8.18–11.9 g/100 g), lipid (0,.78–1.18 g/100 g) and carbohydrate (1.19–3.30 g/100 g) varied significantly during the study period. Saturated fatty acids was the dominant group, except in December when polyunsaturated fatty acids showed the highest proportion (43% of total FAs). Fatty acids of the n3 group were dominant with docosahexaenoic and eicosapentaenoic acids. Highest n3/n6 ratios were recorded in spring-summer specimens, with values > of 5. The results showed a better nutritional quality of scallops in May, July and December.
Keywords: Scallop; Proximate composition; Fatty acids; Central Mediterranean Sea; Quality indeces